Synthesis and photophysical properties of meso‐aminophenyl‐substituted heptamethine dyes as potential leads to new contrast agents. (23rd May 2019) - Okoh, Okoh Adeyi; Critchley, Megan E.; Bisby, Roger H.; Lawrence, Clare L.; Wainwright, Mark; Smith, Robert B.
Abstract : The series of rigid meso ‐aminophenyl‐substituted heptamethine dyes presented herein exhibit surprising fluorescence properties, demonstrating larger Stokes shifts when compared with both structurally similar rigid meso ‐chlorophenyl and linear heptamethine dyes. Based on their photophysical properties, these are of considerable importance to the development of contrast agents, within biology and medicine.